LINC01094 accelerates the metastasis of hepatocellular carcinoma via the miR-26b-3p/MDM4 axis: LINC01094 accelerates HCC metastasis - Mao, Yingmin; Hu, Zhe; Zeng, Yunjian; Zhou, Yuqi; Shi, Zili (Cellular and Molecular Biology, 2023)
To elucidate the role of LINC01094 in accelerating the metastatic potential of hepatocellular carcinoma (HCC) via the miR-26b-3p/MDM4 axis. Differential levels of LINC01094 in clinical samples of HCC and their influence on pathological indicators of recruited HCC patients were detected. Hep3B and SK-HEP-1 cell lines with stable knockdown of LINC01094 were generated by shRNA transfection, followed by detection of migration and invasion by Transwell and wound healing assay. Bioinformatic analysis, dual-luciferase reporter assay and rescue experiments were conducted to assess the interaction between LINC01094 and the miR-26b-3p/MDM4 axis. LINC01094 was upregulated in clinical samples of HCC and its level was linked to the incidences of lymphatic and distant metastasis of HCC patients. Knockdown of LINC01094 weakened migratory and invasive abilities in Hep3B and SK-HEP-1 cells. MiR-26b-3p was the downstream target of LINC01094, which was lowly expressed in HCC tissues and negatively correlated to the LINC01094 level. Moreover, MDM4 was the target gene of miR-26b-3p, which was highly expressed in HCC tissues and negatively correlated to the miR-26b-3p level. Rescue experiments showed that the knockdown of miR-26b-3p could reverse the inhibited metastasis in Hep3B and SK-HEP-1 cells with a stable knockdown of LINC01094. LINC01094 accelerates the metastasis of HCC via the miR-26b-3p/MDM4 axis, which is a potential biomarker and therapeutic target to be utilized in clinical practice.